2007
DOI: 10.1152/ajpheart.00987.2006
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid one-dimensional/Womersley model of pulsatile blood flow in the entire coronary arterial tree

Abstract: Huo Y, Kassab GS. A hybrid one-dimensional/Womersley model of pulsatile blood flow in the entire coronary arterial tree. Am J Physiol Heart Circ Physiol 292: H2623-H2633, 2007. First published January 5, 2007; doi:10.1152/ajpheart.00987.2006.-Using a frequency-domain Womersley-type model, we previously simulated pulsatile blood flow throughout the coronary arterial tree. Although this model represents a good approximation for the smaller vessels, it does not take into account the nonlinear convective energy lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 33 publications
(39 reference statements)
1
61
0
1
Order By: Relevance
“…Huo and Kassab (25,26) validated pulsatile flow simulations from a 1D coronary network model against measurements in isolated, arrested, and vasodilated pig hearts, but the waveforms were not representative of the in situ beating heart and did not contain high-frequency transients. Rumberger and Nerem (54) and Guiot et al (21) compared measured flow waveforms with (71) compared measured and 1D modelsimulated flow waveforms in a single patient; however, the focus was on gross changes to the flow waveform that could likely also be predicted by a 0D model.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Huo and Kassab (25,26) validated pulsatile flow simulations from a 1D coronary network model against measurements in isolated, arrested, and vasodilated pig hearts, but the waveforms were not representative of the in situ beating heart and did not contain high-frequency transients. Rumberger and Nerem (54) and Guiot et al (21) compared measured flow waveforms with (71) compared measured and 1D modelsimulated flow waveforms in a single patient; however, the focus was on gross changes to the flow waveform that could likely also be predicted by a 0D model.…”
Section: Model Validationmentioning
confidence: 99%
“…That these effects play a role in shaping the coronary arterial flow waveform was first suggested by Rumberger et al (54,55) on the basis of flow transients ("oscillations") observed in early systole and diastole in the left anterior descending artery of horses, features that are also evident in published waveforms from humans and other species (5,14,38,76). More recently, therefore, a number of one-dimensional (1D) or multiscale (i.e., combined 0D/1D) models of the coronary circulation, which are best suited to the study of wave propagation effects, have been described (25,45,52,57,58,71). Validation of such models requires direct comparison of simulated and experimental waveform shapes, including any high-frequency flow transients.…”
mentioning
confidence: 99%
“…In particular, the value of the Young modulus E S for each arterial segment has been taken from [2] (for the body and the cerebral parts) and from [28] (for the coronaries). The Poisson ratio m S has been set equal to 0:5, as the arterial wall is assumed to be incompressible.…”
Section: Model Predictionsmentioning
confidence: 99%
“…The classic linear analytical solution known as Womersley flow [42] is a Fourier technique and enables calculation of axi-symmetric velocity profiles by treating each harmonic separately and adding the results together. This technique is commonly used [1,29,36] along with 1D electrical analogs [15] but these do not account for non-linear effects, which are important particularly in the large arteries [5,21,43]. The non-linear equations have been discretized using the finite difference method [2,7,44], as well as various other methods such as the characteristic [16], Galerkin least-squares [6] and discontinuous Galerkin methods [3][4][5].…”
mentioning
confidence: 99%